POVERTY VULNERABILITY AND COPING STRATEGIES AMONG HOUSEHOLDS OF CASSAVA PRODUCERS AND PROCESSORS IN OYO STATE, NIGERIA - Olurinde, K. O.; Adewumi, M. O. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study analysed poverty vulnerability and coping strategies among households of cassava producers and processors in Oyo State, Nigeria. It described the socio-economic characteristics of the respondents; estimated the households’ poverty vulnerability levels; and analysed the poverty coping strategies adopted by the households. Primary data were sourced through the use of questionnaire from 99 cassava producers, 71 gari processors, and 62 cassava flour processors making a total of 232 respondents who were randomly and proportionately selected from the membership register of their respective associations. Descriptive statistics and quantile regression (of the 50th percentile) were used to analyse the data collected. Results revealed that cassava production is male-dominated (85%) while gari processing (87% female) and cassava flour processing (83% female) were female-dominated respectively. The mean age of the cassava producers was 47.7 years, gari processors (45.7 years) and cassava flour processors, 46.6 year, The highest mean number of successful years spent in school (10.5 years) was found among cassava producers Factors found to have significant effects at 5% percent level of significance on the poverty vulnerability status of the households as a result of their effect on the future per capita consumption of the households include household size (-821.68), asset ownership (0.000056), expenditure on treatment of illnesses (-0.0056), price shock (-0.0021), among others. Percentage of households found to be vulnerable to poverty in a year’s time (27.59%) is lower than those who are currently poor (33.62%). The most prevalent coping strategies were reduction of expenditure on transportation costs (mean = 2.92, 1st), reduction of clothing expenses (mean = 2.90, 2nd), use of dirty cooking fuels (mean = 2.82, 3rd) all at a high empirical level of adoption given a mean of mean of 2.42. The study concluded that majority of the cassava producing and processing households in the study area are not vulnerable to poverty as their engagement in cassava value chain acted as buffer against economic shocks. It therefore, recommended, among other things, that the households should invest more along the cassava value chain to further improve their economic resilience.